Psychometric Properties of the Persian Version of Self-Management Scale for a Sample of Iranian Patients With Epilepsy - Dehghan Nayeri, Nahid (Nurs Midwifery Stud, 2013)
BACKGROUND: Despite the importance of self-management in epileptics, no instrument has been developed or validated in Iran. Since self-management is a multi-dimensional construct, having a valid and reliable instrument for measuring this compound construct is crucial. OBJECTIVES: This study aims to validate the Persian version of the self-management scale and provide a valid and reliable tool to measure self-management of patients with epilepsy. PATIENTS AND METHODS: This is a methodological psychometric study. Construct , face and content validity was calculated on 200 samples after translation. Tool reliability was examined by using two methods: internal consistency and test-retest. Finally, the modified model was presented using exploratory factor analysis for the Iranian version of the tool. RESULTS: The validity of all items was above 0.63 and their content validity indexes (0.81-1) were appropriate. Construct validity, exploratory and confirmatory factor analysis confirmed all the dimensions except for some safety and pharmacotherapy items. The overall tool reliability with internal consistency had alpha of 0.77. CONCLUSIONS: Persian version of the self-management scale for patients with epilepsy is valid and reliable to measure the dimensions of self-management in Iranian patients and it can be used to measure epileptics’ self-management. Further research on the safety of this tool is recommended.